The Sertoli cell expressed gene secernin‐1 (Scrn1) is dispensable for male fertility in the mouse. Issue 7 (25th January 2021) - Houston, Brendan J.; Nagirnaja, Liina; Merriner, D. Jo; O'Connor, Anne E.; Okuda, Hidenobu; Omurtag, Kenan; Smith, Craig; Aston, Kenneth I.; Conrad, Donald F.; O'Bryan, Moira K.
Abstract: Background: Male infertility is a prevalent clinical presentation for which there is likely a strong genetic component due to the thousands of genes required for spermatogenesis. Within this study we investigated the role of the gene Scrn1 in male fertility. Scrn1 is preferentially expressed in XY gonads during the period of sex determination and in adult Sertoli cells based on single cell RNA sequencing. We investigated the expression of Scrn1 in juvenile and adult tissues and generated a knockout mouse model to test its role in male fertility. Results: Scrn1 was expressed at all ages examined in the post‐natal testis; however, its expression peaked at postnatal days 7‐14 and SCRN1 protein was clearly localized to Sertoli cells. Scrn1 deletion was achieved via removal of exon 3, and its loss had no effect on male fertility or sex determination. Knockout mice were capable of siring litters of equal size to wild type counterparts and generated equal numbers of sperm with comparable motility and morphology characteristics. Conclusions: Scrn1 was found to be dispensable for male fertility, but this study identifies SCRN1 as a novel marker of the Sertoli cell cytoplasm. Key Findings: SCRN1 is a novel marker of the Sertoli cell cytoplasm. Loss of Scrn1 does not affect male fertility. Scrn1 homologs Scrn2 and Scrn3 do not compensate for Scrn1 loss.